Étude analytique de l'USDA sur les marchés céréaliers de l'UE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A la fin de l'année 2001, le Foreign Agricultural Service...